Mediating Cultural Identity Through Music: A Social Analysis of Tradition and Innovation in Contemporary Composition - Antonyuk, Iryna; et al. (European Journal of Social Science Education and Research, 2026)
The article explores how the synthesis of traditions and innovations in the work of contemporary composers functions not only as an aesthetic phenomenon, but also as a mechanism for the formation of cultural identity and a resource for educational practices. The relevance is due to the need to comprehend music as a socio-cultural and pedagogical tool in the era of globalization. The goal is to identify strategies for mediating identity through stylistic synthesis in the work of G. Zimmer, J. Tiersen, and E. Selvik. The methodology is based on qualitative content analysis and case studies within the framework of a socio-cultural approach, which allows interpreting stylistic features as manifestations of social meanings. Three models are identified: technological hybridization (Zimmer), which constructs a transnational emotional community; methodological low-fi authenticity (Tiersen), which articulates the values ​​of individual sincerity; archaeological reconstruction (Selvik), which reactualizes ethno-cultural memory. These strategies have been shown to promote social cohesion, identity redefinition, and can be integrated into educational programs to develop critical thinking and intercultural competence. The results are important for the sociology of culture, music pedagogy, and cultural policy.